2022
DOI: 10.1126/science.abg0718
|View full text |Cite
|
Sign up to set email alerts
|

A chromosomal inversion contributes to divergence in multiple traits between deer mouse ecotypes

Abstract: How locally adapted ecotypes are established and maintained within a species is a long-standing question in evolutionary biology. Using forest and prairie ecotypes of deer mice ( Peromyscus maniculatus ), we characterized the genetic basis of variation in two defining traits—tail length and coat color—and discovered a 41-megabase chromosomal inversion linked to both. The inversion frequency is 90% in the dark, long-tailed forest ecotype; decreases across a habitat transition; and is abs… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
63
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(91 citation statements)
references
References 85 publications
2
63
0
Order By: Relevance
“…We took advantage of previous work on two populations, representing forest and prairie deer mouse ecotypes (populations c and e, Fig. 4a), which are well characterized and widespread 20 . Forest and prairie mice show many pronounced phenotypic differences (for example, coat colour, tail length, foot length) despite ongoing gene flow.…”
Section: Multiple Inversions Contribute To Local Adaptationmentioning
confidence: 99%
See 2 more Smart Citations
“…We took advantage of previous work on two populations, representing forest and prairie deer mouse ecotypes (populations c and e, Fig. 4a), which are well characterized and widespread 20 . Forest and prairie mice show many pronounced phenotypic differences (for example, coat colour, tail length, foot length) despite ongoing gene flow.…”
Section: Multiple Inversions Contribute To Local Adaptationmentioning
confidence: 99%
“…Forest and prairie mice show many pronounced phenotypic differences (for example, coat colour, tail length, foot length) despite ongoing gene flow. We previously identified an inversion on chromosome 15 (inv15.0) that contributes to phenotypic divergence between these ecotypes 20 . Returning to this system, we found that multiple newly identified inversions were also major contributors to differentiation between these populations.…”
Section: Multiple Inversions Contribute To Local Adaptationmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent genome-scale studies have illuminated wide-ranging impacts of supergene evolution on complex phenotypes across diverse taxa (e.g. Schwander et al, 2014 ; Pearse et al, 2019 ; Hager et al, 2022 ; Joron et al, 2011 ; Kunte et al, 2014 ; Kess et al, 2019 ; Lundberg et al, 2017 ; Roberts et al, 2009 ; Sanchez-Donoso et al, 2022 ; Funk et al, 2021 ). Currently, the mechanisms by which functionally divergent supergene haplotypes evolve in the face of multiple evolutionary forces remain poorly understood, presenting a critical gap in knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…For example, loci that are locally adaptive can benefit from inversions since they can be co-inherited as an adaptive multi-loci haplotype and protected from recombination with non-adaptive alleles (Kirkpatrick and Barton 2006). Numerous non-model systems have been observed to have inversions with adaptive significance: sunflower (Todesco et al 2020), monkeyflower (Lowry and Willis 2010), rainbow trout (Leitwein et al 2017), Atlantic cod (Barth et al 2017; Sodeland et al 2022), stickleback (Jones et al 2012), deer mice (Hager et al 2022; Harringmeyer and Hoekstra 2022).…”
Section: Introductionmentioning
confidence: 99%